1937
DOI: 10.1002/cber.19370700551
|View full text |Cite
|
Sign up to set email alerts
|

Über die Oxydation des Cholesterins mit seleniger Säure

Abstract: B u t r n a n d t , H a u s m n n n il'her d i e O x~d n t i o i~ Jahrg 70 Adolf Rutenandt und EdgarHausmann: ffber die Oxydation des Cholesterins mit seleniger Saure. Ans dem Organ.-chem. Institut (1. Techn. Hochsrhule, DariziR-I,:ingfiihr, und d . Kaiser-Wilhdm-Institut fiir I3iochcmie, Ber1in~T)alilrm.l (Bingegangen am 21. :\pril 1937.)In1 Rahmen unserer 1 intersuchungen iiber die physiologisclie Spezifitat innerhalb der Gruppe der Keiindriisenhornione liaben wir uns seit langerer Zeit beiniiht, s a u e r s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1937
1937
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Oppenauer oxidation of the triol yields clionastanol-5-dione-3,6 (IV). Rosenheim (8) and Butenandt (9) have shown that the oxidation of cholesterol with selenium dioxide gives rise to the formation of the two allylic isomers: 4-hydroxycholesterol, [a]D -60°, and cholestene-4,5-diol-3,6, [a]D +6°. Oxidation of clionasteryl acetate with selenium dioxide by Butenandt's method gives an acetate which upon hydrolysis yields a diol, C29H60O2, [a]" + 8°.…”
mentioning
confidence: 99%
“…Oppenauer oxidation of the triol yields clionastanol-5-dione-3,6 (IV). Rosenheim (8) and Butenandt (9) have shown that the oxidation of cholesterol with selenium dioxide gives rise to the formation of the two allylic isomers: 4-hydroxycholesterol, [a]D -60°, and cholestene-4,5-diol-3,6, [a]D +6°. Oxidation of clionasteryl acetate with selenium dioxide by Butenandt's method gives an acetate which upon hydrolysis yields a diol, C29H60O2, [a]" + 8°.…”
mentioning
confidence: 99%